2010
DOI: 10.1073/pnas.0910117107
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine effects on mouse incentive-learning and human addiction are linked to α2 subunit-containing GABA A receptors

Abstract: Because GABA A receptors containing α2 subunits are highly represented in areas of the brain, such as nucleus accumbens (NAcc), frontal cortex, and amygdala, regions intimately involved in signaling motivation and reward, we hypothesized that manipulations of this receptor subtype would influence processing of rewards. Voltageclamp recordings from NAcc medium spiny neurons of mice with α2 gene deletion showed reduced synaptic GABA A receptor-mediated responses. Behaviorally, the deletion abolished cocaine's ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
125
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(144 citation statements)
references
References 34 publications
12
125
3
4
Order By: Relevance
“…This would suggest that the activation of the a2-and a3-GABA A -Rs in the VTA would inhibit dopaminergic projections from VTA to the NAcc, the opposite of a rewarding effect. Thus, it is likely that the activation of a2-and a3-containing GABA A -Rs in other parts of the reward circuitry is important for the reward-enhancing effects of diazepam in ICSS, similar to the findings by Dixon et al (2010) showing that the NAcc a2-containing GABA A -Rs are required for certain drug effects of cocaine.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This would suggest that the activation of the a2-and a3-GABA A -Rs in the VTA would inhibit dopaminergic projections from VTA to the NAcc, the opposite of a rewarding effect. Thus, it is likely that the activation of a2-and a3-containing GABA A -Rs in other parts of the reward circuitry is important for the reward-enhancing effects of diazepam in ICSS, similar to the findings by Dixon et al (2010) showing that the NAcc a2-containing GABA A -Rs are required for certain drug effects of cocaine.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, it is possible that the prefrontal, subicular, and amygdalar excitatory inputs into the NAcc, as well as NAcc output to downstream structures, may be controlled by a2-GABA A -Rs, while the dopaminergic inputs from VTA onto NAcc may be controlled by a1-GABA A -Rs, resulting in a dissociation between the motivational (ie, wanting) and appetitive (ie, liking) components of reward. A recent study provides some initial evidence for the view that the a2-containing GABA A -Rs of the NAcc play a pivotal role in the incentive effects of drugs of abuse by modulating the activity of medium spiny neurons (Dixon et al, 2010), supporting a role for these receptors in certain incentive motivational processes as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we showed recently that chronic cocaine increases the expression of several GABA A R subunits, including Gabra1, Gabra2, and Gabrb2 in NAc and that GABA A R antagonism blocks behavioral plasticity to cocaine (Kennedy et al, 2013), findings consistent with earlier studies (Dixon et al, 2010;Heiman et al, 2008). In contrast, we show here that chronic morphine decreases levels of several GABA A R subunits, including Gabra2 and Gabrd, in whole NAc and that GABA A R antagonism in this region robustly enhances morphine reward.…”
Section: Discussioncontrasting
confidence: 51%
“…Such morphine-induced downregulation of GABA A R subunits is even more apparent when D1-type MSNs are examined selectively (see below). Interestingly, mRNA expression levels of Gabra2, which encodes the GABA A R-a2 subunit and is implicated in reward learning and behavioral sensitization as well as human cocaine addiction (Dixon et al, 2010), is regulated oppositely in the NAc by morphine vs cocaine. A previous study showed that GABA A R-a2 subunit is not directly associated with cocaine reward as evidenced by no alterations in cocaine CPP and conditioned reinforcement in Gabra2-deficient mice (Dixon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%